Immunophenotypic transformation in relapsed/refractory mantle cell lymphoma treated with human anti-CD5 chimeric antigen receptor T cells: A Case Report - He, Sha; Mao, Xia; Cheng, Zhaoting; Zhu, Xiaojian; Xiao, Min; Zhou, Jianfeng (Frontiers in Hematology, 2022)
Relapsed/refractory (R/R) mantle cell lymphoma (MCL) with resistance to Bruton tyrosine kinase inhibitor and mutated TP53 responds poorly to conventional treatments. Chimeric antigen receptor (CAR) T cell therapy has emerged as one of the most effective treatments for R/R B cell lymphoma. However, no reports of CD5 CAR T cell treatment for MCL have been reported. In this paper, we report an R/R MCL patient with primary resistance to BTK inhibitors and TP53 mutation enrolled in a human CD5 CAR T cell trial. Remission of the primary disease was observed half a month after CAR T cell infusion. However, ascites was observed 2 weeks later. Flow cytometry suggested disease progression and immunophenotypic transformation. CD5 in CAR T cells turned negative and the expression of CD38 was enhanced. The patient was treated with a combination of daratumumab and Gemox (gemcitabine + oxaliplatin), abdominal distension and pain were markedly reduced, and ascites disappeared. We report the first case of human CD5 CAR T cell treatment for a patient with R/R MCL, providing insight on treatment strategies for such patients.